2014
DOI: 10.1021/am502370t
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of Tungsten Surfaces by Low-Flux Helium Plasma Treatment and Helium Incorporation via Magnetron Sputtering

Abstract: The effect of helium on the tungsten microstructure was investigated first by exposure to a radio frequency driven helium plasma with fluxes of the order of 1 × 10(19) m(-2) s(-1) and second by helium incorporation via magnetron sputtering. Roughening of the surface and the creation of pinholes were observed when exposing poly- and nanocrystalline tungsten samples to low-flux plasma. A coating process using an excess of helium besides argon in the process gas mixture leads to a porous thin film and a granular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 40 publications
(97 reference statements)
1
22
0
Order By: Relevance
“…For each step a new fresh 20 nm tungsten film was deposited on silicon wafer by means of pulsed-DC magnetron sputtering of a 99.95% pure W target (details about the deposition parameters can be found in ref. 40).…”
Section: Surface Study In a Conventional Stainless Steel Vacuum Chambermentioning
confidence: 99%
“…For each step a new fresh 20 nm tungsten film was deposited on silicon wafer by means of pulsed-DC magnetron sputtering of a 99.95% pure W target (details about the deposition parameters can be found in ref. 40).…”
Section: Surface Study In a Conventional Stainless Steel Vacuum Chambermentioning
confidence: 99%
“… 4 5 6 7 More recently, significant surface modifications were observed on tungsten under low-energy He ion irradiation, with ion energies below the threshold for damage creation, and investigated as a function of surface temperature, ion flux and exposure time. 8 9 10 11 These studies revealed the formation of a fine nanostructure exhibiting a high porosity of up to 90% and high light absorption. 12 13 14 The size of those nanostructures and thickness of the nanostructured layer could be controlled by surface temperature and plasma exposure time, respectively.…”
mentioning
confidence: 91%
“…However, other potential applications have been demonstrated such as annihilation of dislocations in GaN [12], reducing the threading dislocation density via the enhancement of the strain relaxation of SiGe/Si heterostructures [13], * marie-laure.david@univ-poitiers.fr the proximity gettering of metallic impurities [14], or the fabrication of ultrathin buried oxide layers in silicon [15]. Finally, low-energy helium plasma treatments have recently received considerable interest for nanostructuration of surfaces with applications in domains of energy conversion and storage devices, by both bottom-up [16] or top-down approaches [17,18]. In particular, nanopores in amorphous silicon coatings produced using such methods have been revealed to contain a high helium density [19].…”
Section: Introductionmentioning
confidence: 99%